The Relationship between Stock Price Risk and Institutional Investment with Stock Returns with Emphasis on the Moderating Role of Liquidity Ratio in Companies Listed on the Tehran Stock Exchange - Masoumi, Habibollah (Mathematical Statistician and Engineering Applications, 2023)
Stock returns are one of the most important issues in finance. Today, the process of examining the profitability and stock returns of companies is one of the most important issues for managers, investors, creditors and other stakeholders, and the results are the basis of many decisions inside and outside companies. The main purpose of this study is to investigate the relationship between stock price fall risk and institutional investment with stock returns with emphasis on the adjusting role of the liquidity ratio. The statistical sample of the research is 132 companies. The research method is descriptive-correlation with applied approach. The method of data collection in the theoretical foundations section is the library method and in the hypotheses testing section is the method of documenting financial statements. In general, the method of testing hypotheses is the method of correlation and multiple regression. The results showed that there is a significant inverse relationship between stock price risk and stock returns. There is a direct and significant relationship between institutional investment and stock returns. The company’s liquidity also weakens the inverse relationship between stock price risk and stock returns and strengthens the direct relationship between institutional investment and stock returns.